The Effect of Job Stress on Turnover Intention Through Perceived Organisational Support as a Moderator in Marketing Employees - Tobing, Julius; Aisyah, Siti; Hardjo, Suryani (Yayasan Ilomata, 2025)
Although there is recognition of the level of job stress, the link with turnover intention is clearly evident. Therefore, the following research questions are posed: Does job stress have a direct effect on turnover intention? Furthermore, to what extent does job stress have an indirect effect on turnover intention through perceived organizational support? While job stress is acknowledged as a significant factor, it does not fully capture the concept of perceived organizational support, which is crucial for individual decision-making and well-being. Persistent turnover intention is not solely caused by job stress; perceived organizational support plays an important role in long-term career success. However, a review of the existing literature reveals a lack of studies specifically addressing the mediating role of perceived organizational support in the relationship between job stress and turnover intention. This research gap calls for further exploration.This study uses a non-experimental quantitative approach with a case study design. The goal is to observe a specific sample group rather than to generalize the research findings. The sample was selected through a process based on the level of turnover intention at the research location. Data were collected using three scales and analyzed through mediation analysis. The findings of this study indicate that the initial hypothesis, which states that job stress has a direct effect on employee turnover intention, is supported. In addition, the second hypothesis is also accepted, indicating that job stress has an indirect effect on turnover intention through perceived organizational support. Conclusions and further recommendations will be elaborated in the subsequent discussion.